PCR based SNPs marker for specific characterization of English walnut (Juglans regia L.) cultivars - Ciarmiello, Loredana F; Piccirillo, Pasquale; Pontecorvo, Giovanni; De Luca, Antonio; Kafantaris, Ioannis; Woodrow, Pasqualina (Molecular biology reports, 2011)
English walnut (Juglans regia L.) is the most economically important species from all the 21 species belonging to the genus Juglans and is an important and healthy food as well as base material for timber industry. The aim of this study was to develop a simple technique for specific characterization of English walnut using DNA method. The first and second internal transcribed spacers (ITS1 and ITS2) as well as the intervening 5.8S coding region of the rRNA gene for 18 cultivars of J. regia L. isolated from different geographic origins were characterized. The size of the spacers sequences ranged from 257 to 263 bases for ITS1 and from 217 to 219 bases for ITS2. Variation of GC contents has also been observed and scored as 55-56.7 and 57.1-58.9% for ITS1 and ITS2, respectively. This data exhibited the presence of polymorphism among cultivars. Alignment of the ITS1-5.8S-ITS2 sequences from 18 walnut cultivars showed that there were 244 single nucleotide polymorphisms (SNPs) and 1 short insertion-deletion (indel) at 5′ end ITS1. Amplification refractory mutation system strategy was successfully applied to the SNP markers of the ITS1 and ITS2 sequences for the fingerprinting analysis of 17 on 18 walnut cultivars. The prediction of ITS1 and ITS2 RNA secondary structure from each cultivar was improved by detecting key functional elements shared by all sequences in the alignments. Phylogenetic analysis of the ITS1-5.8S-ITS2 region clearly separated the isolated sequences into two clusters. The results showed that ITS1 and ITS2 region could be used to discriminate these walnut cultivars.